Pararhexoacrodictys (Incertae sedis, Ascomycetes) gen. nov., new combinations and new records of hyphomycetes from Brazil - Cantillo, Taimy; de Almeida, Davi Augusto Carneiro; Monteiro, Josiane Santana; Gusmão, Luís F.p. (Phytotaxa, 2019)
In this study, Pararhexoacrodictys gen. nov., with Pa. catolensis as the type species is described and compared with morphologically similar Acrodictys-like genera. The new genus is phenotypically similar to both Rhexoacrodictys and Pseudoacrodictys but separated by other morphological characters. Pa. minima sp. nov. and two combinations, Pa. balansae and Pa. magnicornuata, are introduced, and new records of Pseudoacrodictys and Shrungabeeja are also registered for South America and the Neotropics.